Impact of blended learning on human science students at the International Islamic University Malaysia (IIUM) - Nazari, Nur Syahirah; Wok, Saodah (Penebit KUIM, 2017)
Blended learning is collaborative learning between classroom learning and online learning. Blended learning was developed to enhance students’ performance to increase their critical thinking and learning process. The objectives of this study are (1) to measure the level of perception, attitude, impact, behavior and satisfaction on blended learning; (2) to determine the relationship among perception, attitude, behavior, impact and satisfaction on blended learning; (3) to determine the best predictor for students’ performance based on blended learning. The social Learning Theory (Bandura, 1977) is used in this study to explain perception, attitude, impact, behavior and satisfaction on blended learning. The study is using the quantitative research design with survey questionnaires, which were distributed to 150 respondents. The results show that there are positive relationships among all variables.¬ However, the awareness of blended learning among students is low but their attitude towards blended learning is high